(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In recent decades, air pollution has become one of the most significant challenges shaping the environment, public health, and sustainable development of nations. Despite the development of international environmental initiatives and the implementation of environmental standards, pollutant emissions continue to rise in most densely populated regions of the world. Urbanization, industrialization, the growth of the vehicle fleet, the expansion of the energy sector, and inadequate infrastructure modernization are leading to a steady increase in concentrations of suspended particles, nitrogen oxides, sulfur compounds, ozone, and volatile organic compounds. These processes create unfavorable conditions under which air ceases to fulfill its natural function of supporting human life and ecosystems.